2006 IEEE Information Theory Workshop
DOI: 10.1109/itw.2006.1633801
|View full text |Cite
|
Sign up to set email alerts
|

Punctured vs Rateless Codes for Hybrid ARQ

Abstract: Two incremental redundancy hybrid ARQ (IR-code. Initially, only the systematic part of the codeword and HARQ) schemes are compared: one is based on LDPC code a selected number of parity bits are transmitted. The selected ensembles with random transmission assignments, the other parity bits together with the systematic bits form a codeword of is based on recently introduced Raptor codes. A number of a bits totherwtte sematic bis codeword important issues, such as rate and power control, and error rate a puctred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 14 publications
0
41
0
Order By: Relevance
“…The discrete-input continuousoutput memoryless channel's (DCMC) capacity curve is also shown. The Raptor code and the punctured LDPC benchmarker codes follow the same designs presented in [14]. The decoder employs the well-known sum-product algorithm, limited to a maximum of 200 iterations.…”
Section: Degree Distributionmentioning
confidence: 99%
“…The discrete-input continuousoutput memoryless channel's (DCMC) capacity curve is also shown. The Raptor code and the punctured LDPC benchmarker codes follow the same designs presented in [14]. The decoder employs the well-known sum-product algorithm, limited to a maximum of 200 iterations.…”
Section: Degree Distributionmentioning
confidence: 99%
“…Both methods have their own limitations and typically a combination of both techniques is generally preferred [233], [291]. The striking similarities of rateless coding with HARQ were first exploited by Soljanin et al in [292], [293], who compared the performance of Raptor codes as well as punctured LDPC codes for transmission over the BIAWGN channel. Their results demonstrated that the family of Raptor codes represents a more suitable alternative than punctured LDPCs for covering an extensive range of channel SNRs (and thus rates).…”
Section: B Other Rateless Codes and Their Performance Over Noisy Chamentioning
confidence: 99%
“…Average throughput (bits/channel use) performance for transmission over the BIAWGN channel versus SNR (dB) using the proposed reconfigurable rateless codes as well as for the Raptor code [254] and the incremental-redundancy-based HARQ schemes employing punctured regular LDPC codes having R = 0.8 and 0.9 and an optimized punctured half-rate irregular LDPC code. The Raptor code and the punctured LDPC benchmarker codes followed the design presented in [292], [293]. The decoder employed the SPA and was limited to a maximum of 200 iterations.…”
Section: B Possible Future Research Directionsmentioning
confidence: 99%
“…The performance of rateless codes, such as LT and Raptor codes, were compared with punctured codes in [17] and were further investigated in a wireless relay-aided network in [18]. Another coding scheme designed for cooperative communication is constituted by the HARQ scheme of [19,20].…”
Section: Introductionmentioning
confidence: 99%